Suitability of Some Climatic Parameters for Grapevine Cultivation in South Africa, with Focus on Key Physiological Processes - Hunter, J.J.; Bonnardot, V. (South African Journal of Enology and Viticulture, 2011)
To optimise the functioning of the grapevine in a specific environment and to improve grape and wine quality, suitability of climatic parameters for key grapevine physiological processes needs to be assessed at fine scales. This paper presents methodology using hourly weather data in three wine producing regions of South Africa (Coastal Region – Stellenbosch district; Breede River Valley – Robertson district; Central Orange River Region – Upington district) during the pre- (November to December) and post-véraison (January to February) periods. Durations inside and outside an optimum climatic range and of extreme climatic conditions were calculated over a 5-year period (1999/2000 to 2003/2004) to quantify a climatic profile related to grapevine physiological requirements. Climatic requirements for optimum photosynthetic activity were defined as follows: temperature 25°C to 30°C, windspeed <4 m/s, relative humidity 60% to 70%. Unsuitable climatic periods for vine performance were calculated as <20°C and >35°C, >4m/s, <50% and >80%. A coefficient was assigned to each climatic parameter according to an assumed importance level for physiological processes. Optimum temperature requirements for other physiological parameters were also investigated. A diurnal minimum/maximum temperature range of 25°C to 30°C was used for sugar content and organic acid levels and a maximum night/day temperature range of 15°C/25°C for colour and flavour. Light intensity was accepted as being sufficient. Stations were classified according to their potential for meeting the climatic requirements of each physiological parameter. Marked variation in climatic profiles and available time for optimal physiological functioning occurred between regions. All factors considered, the climatic profile of the Coastal Region (Stellenbosch district) seemed to best satisfy the climatic requirements of the physiological parameters studied.